Pengembangan Bahan Ajar Flipbook pada Mata Pelajaran IPAS Kelas IV SDN 03 Pontianak Selatan - Nur Fadhila; Siti Halidjah; Dyoty Auliya Vilda Ghasya (ALSYS, 2026)
Although developments in educational technology have driven the need for interactive and practical learning resources, the limited availability of technology-based teaching materials still causes the learning process to not yet run optimally. This study aimed to develop flipbook-based teaching materials for Grade IV IPAS that are feasible for use as a learning resource for students. This study used the Research and Development (R&D) method with the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The sources of the research data included responses from expert validators, the homeroom teacher, and 31 Grade IV A students at SDN 03 Pontianak Selatan. Data were collected through interviews and questionnaires, and were then analyzed descriptively to assess the feasibility of the product. The results showed that Validator I gave an average score of 4.8 with a percentage of 96% and Validator II gave an average score of 4.1 with a percentage of 83%, both of which were in the very good category. The teacher’s response obtained an average score of 4.2 with a percentage of 84%, which was in the very good category. Meanwhile, student responses in the Phase I trial reached 92% and in Phase II reached 93%, both of which were in the very good category. These findings show that the developed flipbook-based teaching materials were declared feasible for use as a learning resource for Grade IV IPAS. This study contributes to the development of interactive digital teaching materials in elementary schools and provides practical implications for teachers in providing learning resources that are more engaging, easily accessible, and suited to learning needs.